Development of a Harmonized Protocol for Measurement of Foliar Wash‐off Parameters: First Results. (20th December 2022) - Hand, Laurence H.; Hellpointner, Eduard; Volz, Petra; Perry, Alexandra; Rieder, Benjamin; Gourlay, Victor; Hüben, Michael; Popescu, Marian
Abstract: The foliar wash‐off coefficient is a parameter used by environmental fate models to estimate the amount of chemical removed from leaf surfaces by rainfall. In the European Union it is used by FOCUS surface water models to estimate soil loadings following rainfall after leaf surfaces have been treated with plant protection products. Currently, a default value of 0.5/cm is assumed for this parameter, although there is provision to provide experimental data to replace this default. The European Food Safety Authority proposed to increase the default parameter value to 1.0/cm. This increases the need for experimental refinement studies. However, no guidance for a harmonized protocol exists to estimate this parameter. We describe the results of a ring‐test conducted to start a process of developing a harmonized experimental protocol to measure the foliar wash‐off parameters, conducted by several laboratories across Europe. The proposed design uses whole plants (rather than individual leaves) to retain as much realism as possible. The extent of wash‐off is then determined by comparison of compound residues in two sets of plants (with and without a defined rainfall event) measured using a fully validated crop residue method. This initial ring test used tebuconazole (Folicur EW 250) sprayed at 100 g ai/ha onto tomato plants at BBCH25. Each laboratory measured the residues before and after a rainfall event of 20 mm/h for 1 h and calculated the percentage of wash‐off from these data. There was good agreement across the eight participating laboratories with a mean percentage of wash‐off of 66.8% and a 95% confidence interval of ±11.8%. Determination of robust wash‐off parameters was therefore considered feasible using the proposed test design. Environ Toxicol Chem 2023;42:535–541. © 2022 SETAC Abstract : Development of a harmonized protocol for measurement of foliar wash‐off parameters: first results.